Standards for the care of people with cystic fibrosis; establishing and maintaining health - Southern, Kevin W; Addy, Charlotte; Bell, Scott C; Bevan, Amanda; Borawska, Urzula; Brown, Catherine; Burgel, Pierre-Régis; Button, Brenda; Castellani, Carlo; Chansard, Audrey; Chilvers, Mark A; Davies, Gwyneth; et al. (Journal of cystic fibrosis, 2024)
This is the second in a series of four papers updating the European Cystic Fibrosis Society (ECFS) standards for the care of people with CF. This paper focuses on establishing and maintaining health. The guidance is produced using an evidence-based framework and with wide stakeholder engagement, including people from the CF community. Authors provided a narrative description of their topic and statements, which were more directive. These statements were reviewed by a Delphi exercise, achieving good levels of agreement from a wide group for all statements. This guidance reinforces the importance of a multi-disciplinary CF team, but also describes developing models of care including virtual consultations. The framework for health is reinforced, including the need for a physically active lifestyle and the strict avoidance of all recreational inhalations, including e-cigarettes. Progress with cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapy is reviewed, including emerging adverse events and advice for dose reduction and interruption. This paper contains guidance that is pertinent to all people with CF regardless of age and eligibility for and access to modulator therapy.
Keywords: látky ovlivňující dýchací systém; Cystic Fibrosis Transmembrane Conductance Regulator; mutace; Mutation; protein CFTR; Humans; Respiratory System Agents; Electronic Nicotine Delivery Systems; Cystic Fibrosis; lidé; cystická fibróza; systémy dodávající nikotin elektronicky